Treatment and outcome variation in out-of-hospital cardiac arrest among four urban hospitals in Detroit. (April 2023) - Mathew, Shobi; Harrison, Nicholas; Ajimal, Sukhwindar; Silvagi, Ryan; Reece, Ryan; Klausner, Howard; Levy, Phillip; Dunne, Robert; O'Neil, Brian
Abstract: Aims: To determine whether out-of-hospital cardiac arrest (OHCA) post-resuscitation management and outcomes differ between four Detroit hospitals. Introduction: Significant variation exists in treatment/outcomes from OHCA. Disparities between hospitals serving a similar population is not well known. Methods: Retrospective OHCA data was collected from the Detroit-Cardiac Arrest Registry (DCAR) between January 2014 to December 2019. Four hospitals were compared on two treatments (angiography, do not resuscitate (DNR)) and two outcomes (cerebral performance category (CPC) ≤ 2, in-hospital death). Models for death and CPC were tested with and without coronary angiography and DNR status. Results: 999 patients at hospitals A - D differed (p < 0.05) before multivariable adjustment by age, race, witnessed arrest, dispatch-emergency department (ED) time, TTM, coronary angiography, DNR order, and in-hospital death. Rates of death and CPC ≤ 2 were worse in Hospital A (82.8%, 10%, respectively) compared to others (69.1%, 14.1%). After multivariable adjustment, Hospital A performed angiography less compared to B (OR = 0.17) and was more likely to initiate new DNR status than B (OR = 2.9), C (OR = 16.1), or D (OR = 3.6). CPC ≤ 2 were worse in Hospital A compared to B (OR = 0.27) and D (OR = 0.35). After sensitivity analysis, CPC ≤ 2 odds did not differ for A versus B (OR = 0.58, adjusted for angiography) or D (OR = 0.65, adjusted for DNR). Odds of death, despite angiography and DNR differences, were worse in Hospital A compared to B (OR = 1.87) and D (OR = 1.81). Conclusion: Differing rates of DNR and coronary angiography was associated with observed disparities in favorable neurologic outcome, but not death, between four Detroit hospitals.